Penentuan Konsentrasi Parasetamol Menggunakan Sensor Elektrokimia Platina (Pt) dengan Teknik Voltametri Siklik - Dwi Hermayantiningsih; Zahrotun Nafisah; Remi Ayu Pratika (Yayasan Literasi Sains Indonesia, 2026)
The aim of this study was to determine the concentration of paracetamol in tablet formulations using cyclic voltammetry, with a platinum electrode serving as both the working electrode (WE) and the counter electrode (CE), and Ag/AgCl as the reference electrode (RE). Cyclic voltammetry measurements for paracetamol analysis were carried out within a potential range of 0 to 1.5 V with a constant scan rate of 100 mV/s and 0.1 M H₂SO₄ as the electrolyte. The resulting voltammogram profile showed a clear and sharp anodic peak in the potential range of approximately 0.6–1.4 V, indicating the oxidation of the phenolic group present in the paracetamol (C₈H₉NO₂) forming N-acetyl-p-benzoquinone imine (NAPQI) via an electron transfer mechanism on the surface of the platinum working electrode, which functions as the detection sensor. A standard calibration curve was constructed based on the relationship between the concentration of the paracetamol standard solution and the anodic peak current (IA). The linear regression equation obtained is y = 2 × 10-7x + 3 × 10-6. Substituting the sample anode current value into this equation and taking into account a dilution factor of 5, the sample concentration is found to be 1950 ppm. Taking into account the sample volume of 25 mL, sample mass of 500 mg, and tablet mass of 4000 mg, the concentration of paracetamol in a single tablet is calculated to be 390 ppm (equivalent to 390 mg/L).